Imaging in hypertensive heart disease. (February 2011) - Janardhanan, Rajesh; Kramer, Christopher M
Hypertensive heart disease is the target organ response to arterial hypertension. Left ventricular hypertrophy represents an important predictor for cardiovascular events. Myocardial fibrosis, a common end point in hypertensive heart disease, has been linked to the development of left ventricular hypertrophy and diastolic dysfunction. Echocardiography is clinically useful in the detection of left ventricular hypertrophy and the assessment of diastolic function. Although echocardiography is more widely available, cardiac magnetic resonance has been demonstrated to be more reproducible for the estimation of left ventricular mass. Future developments in cardiac magnetic resonance techniques may facilitate the quantification of diffuse fibrosis that occurs in hypertensive heart disease. Thus, advances in cardiac imaging provide comprehensive, noninvasive tools for imaging left ventricular hypertrophy, diastolic dysfunction, myocardial fibrosis and ischemia observed in hypertensive heart disease. The objective of this article is to summarize the state-of-the-art and the future of multimodality imaging of hypertensive heart disease.